THE CORRELATION BETWEEN CUSTOMER RELATIONSHIP MANAGEMENT AND THE INPATIENTS LOYALTY - Rezky Amalia Amal; Syahratul Aeni; Syarfaini Syarfaini; A Syamsiah Adha (Homes Journal = Hospital Management Studies Journal, 2021)
Background :Customer Relationship Management (CRM) as a process to build a relationship between companies and customers by increasing customers value and satisfaction performed by identifying customers by forming perceptions on the products or organizations or services offered through marketers, sellers, services and supporting services which make the customers to be loyal. Objective :The study was aimed at determining the correlation between Customer Relationship Management and the inpatients loyalty at Ibnu Sina Hospital of Makassar in 2017.Method :This study was quantitative research using an obsevational analytic approach with cross sectional study involving 18304 people as research population and 391 samples. Moreover, univariate and bivariate with chi square test were utilized in analysing the data. Result :The results showed that there was a significant correlation between continuity marketing (p=0.000), one to one marketing (p=0.000), and partnering program did not have a significant correlation (p=0.090) with patient loyalty. Conclusion: Ibnu Sina Hospital must be able to manage customer relationship management well to maintain patient loyalty in order to reuse services at the hospital.